Kedma - Amos, Gitai; Yaralova, Helena; Juliano Mer; Menachem Lang; Moni Moshonov; Sendi Bar; Yussuf AbuWarda; Andrei Kashkar (Italy Israel France Agav Hafakot, 2002)
Set seven days before the creation of the state of Israel in May 1948, a small rusted ship, with a group of concentration camp survivors from Shoah, is received at the new territory with open hostility. They are met by British troops, who are shooting at them, and are trying to forbid them from disembarking. As well, the survivors are met with guns blasts being shot by the Jewish secret army, who has come to help them. Only a small group actually succeeds in landing on the small beach, where they are able to experience their first hours in Palestine. Tired and hungry, the hopeful emigrants have then to follow the Jewish forces to immediately take up arms against the Arabs. Unspoken truths from both sides explode in the violent and tragic conflict.
In May 1948, shortly before the creation of the State of Israel, hundreds of immigrants from across Europe arrive in Palestine--only to risk arrest by British troops.
Amos Gitai
Language : English Subtitles : No Subtitles
Keywords: War; Drama